MITM Attack Prevention Using PUF Authentication in Smart Grid - Aruna Gawade, Narendra Shekokar (International Journal of Advanced Science and Technology, 2020)
IoT security is the primary concern with the increasing demand of IoT applications. Smart Grid beingan important IoT application also requires secure data handling. Smart Grid deals withperiodic transmission of smart meter data over the internet. It reflects the gas, water and electricity usage pattern of the customers which is confidential and should be accessible by the legitimate users. Security aspects failure in such scenario, may lead to different types of attacks. So a Smart Grid setup needs proper authentication and key management mechanism to handle this data carefully and securely. PUF digital footprint based authentication algorithm is the best choice in such scenario. In this paper we have proved thatMITM(Man in the middle)can prevented by using lightweight PUF based authentication mechanism.We have also tested the system with NodeMCU setup and proved that the algorithm is safe and resistant to MITM attack.